Design simulation and finite element analysis of piezoresistive microcantilever for human stress measurement / Nina Korlina Madzhi ...[et al.] - Madzhi, Nina Korlina; Ahmad, Anuar; Lee, Yoot Khuan; Abd Rani, Rozina (UiTM Press, 2009)
This work focuses on the design and finite element analysis of a polysilicon-based piezoresistive microcantilever beam for application in human stress measurement. In principle, adsorption of saliva amylase on a functionalized surface of the microfabricated cantilever induces surface stress and consequently the bending of the cantilever beam. In this paper, the microcantilever beam is constructed and bending analysis is performed so that tip deflection of the beam can be predicted. The device is modeled using CoventorWareTM. The structural variation in the piezoresistor design on the cantilever beam is investigated to increase the sensitivity of the microcantilever sensor. The stress distribution and the vertical displacement of the piezoresistive microcantilever designed are studied through simulation. The relative resistance changes in the piezoresistors as a function of the vertical displacements of the microcantilever beam is also investigated. It is found that the deflection displacement increases with length and thickness of piezoresistor. The relative resistance change in the piezoresistors is found to increase when the thickness decreases.